Piracy as Conflict. Discourses on Intellectual Property Rights in Mexico - Aguiar, José Carlos (2010)
This article examines the evolution of intellectual property rights (IPR) protection in relation to anti-piracy actions undertaken by the Mexican government. The ‘war against piracy’ is based on the world trade legal structure. The author’s central argument is that the criminalization of piracy is not the result of a process of national interest which has as its objective the promotion and intensification of intellectual property rights or the rule of law but, rather, emerges from a punitive perspective emanating from networks of international interests and transnational actors characteristic of global neoliberalism.